Islam Di Komering Desa Betung Kec. Semendawai Barat, Kab. Oku Timur, Sumatera Selatan - Ahimsa Pramudia Taaruf (Tanjak: Sejarah dan Peradaban Islam, 2023)
The history of the entry and development of Islam in Komering Betung is one of the phenomena of the development of Islam in Indonesia, especially in South Sumatra. The presence of several ulama in the 16th to 18th centuries in the Komering area was a trigger for the development of Islam in Komering. Of the many ulama, there are 3 ulama who started preaching in Komering, one of which is Tuan Di Pulau (Sayid Hamimul Hamiem) whose grave is currently in Campang Tiga Village, Kec. Cempaka. He is a Komering Muslim figure who is said to be the forerunner of Islam in Komering Betung. Islam in Komering had several triggers for its development, one of which, apart from the ulama who started arriving, was the end of the conflict between the Abung Tribe and the Komering Tribe in Komering in the 17th century. So after the conflict was over, the development of Islam spread further to the Uluan and Ilir areas, assisted by with the presence of Makkah scholars who gradually came to this area in the 18th century AD. Apart from the historical aspect, the discovery of Islamic archaeological objects and material heritage is one of the authentic evidences of Islamic history in Komering Betung.